Methylene Blue as a Photo-Redox Catalyst: The Development Synthesis of Tetrahydrobenzo[b]pyran Scaffolds via a Single-Electron Transfer/Energy Transfer - Mohamadpour, Farzaneh (Frontiers in Chemistry, 2022)
In a green tandem reaction using aldehyde derivatives, malononitrile, and dimedone, a radical tandem Knoevenagel–Michael cyclocondensation reaction of tetrahydrobenzo[b]pyran scaffolds was developed. Using visible light as a sustainable energy source, methylene blue (MB+)-derived photo-excited state functions were employed in an aqueous solution as single-electron transfer (SET) and energy transfer catalysts. The range of yields is quite uniform (81–98%, average 92.18%), and the range of reaction time is very fast (2–7 min, average 3.7 min), and the point mentioned in the discussion is that the procedure tolerates a range of donating and withdrawing groups, while still giving very excellent yields. The reaction is fairly insensitive to the nature of the substituents. Research conducted in this project aims to develop a non-metallic cationic dye that is both inexpensive and widely available for more widespread use. In addition to energy efficiency and environmental friendliness, methylene blue also offers an excellent atom economy, time-saving features, and ease of use. As a result, a wide range of long-term chemical and environmental properties can be obtained. The turnover number and turnover frequency of tetrahydrobenzo[b]pyran scaffolds have been computed. Surprisingly, gram-scale cyclization is a possibility, implying that the technology may be applied in industries.